Assess to improve students' digital skills - Patrício, Maria Raquel (2017)
The European Digital Competence Framework - DigComp is the European Commission's proposal for the set of competences that are essential to all citizens today, identifying and describing the key components of digital competence in terms of knowledge, skills and attitudes. DigComp describes 21 competences, structured in 5 areas of competence (Information and data literacy, Communication and collaboration, Digital content creation, Safety and Problem solving), to use digital technologies in a confident, critical, collaborative and creative way, to achieve the goals related to work, employability, learning, leisure, inclusion and participation in society. The development of digital competence among students plays an important role for all students at all educational levels. It is essential to motivate students to participate in activities that help them develop their digital competence. However, it is necessary to assess the gaps between the desired level of each area to design activities in the classroom, which develop the critical competence areas. Regarding the DigComp 2.1 aims to provide a digital competence model assessment of students to make the analysis of students' needs and thus develop a training plan, curricula and contents, for improvement students’ digital skills, empowering them in an appropriate, positive and responsible use of digital technologies.